Paparan Debu Kayu dan Aktivitas Fisik terhadap Dampak Kesehatan Pekerja Meubel - Herdianti Herdianti; Taufik Fitriyanto; Suroso Suroso (Jurnal Kesehatan Manarang, 2018)
Based on data from the International Labor Organization of the ILO, 1 worker dies every 15 seconds due to workplace accidents and 160 workers suffering from work-related illness. The mortality rate due to occupational accidents and occupational diseases in Indonesia is still high. Occupational disease consists of a causative agent in the workplace. This research is a quantitative descriptive research that aims to find out the description of wood dust and physical activity exposure to health at worker Furniture in CV Semoga Jaya Jambi City in 2017. Population in this research is all labor in furniture CV Semoga Jaya Jambi City 2016 which amount 31 people. Samples in total sampling that amounted to 31 people. The research process conducted on May 15 to June 10 Year 2017 in furniture CV Semoga Jaya Jambi City. Data were analyzed univariat. The result of univariate research showed that most of the respondents (74,2%) had bad exposure (> NAB), most of them (51,6%) had fatigue and most (58,1%) did not suffer from respiratory problems. It is expected that workers use PPE in the form of masks to prevent exposure to dust from wood dust during work. In addition, stretching the muscles during fatigue due to monotonous work attitude. In addition, business owners need to create a special space in each room of production roses that produce wood powder to make the resulting powder not directly exposed or slightly reduce the direct exposure to wood dust dust with workers.